Normalizing diabetes in Delhi: a qualitative study of health and health care. Issue 3 (1st September 2016) - Mendenhall, Emily; McMurry, H. Stowe; Shivashankar, Roopa; Narayan, K.M. Venkat; Tandon, Nikhil; Prabhakaran, Dorairaj
ABSTRACT: The Type 2 diabetes epidemic in India poses challenges to the health system. Yet little is known about how urban Indians view treatment and self-care. Such views are important within the pluralistic healthcare landscape of India, bringing together allopathic and non-allopathic (or traditional) paradigms and practices. We used in-depth qualitative interviews to examine how people living with diabetes in India selectively engage with allopathic and non-allopathic Indian care paradigms. We propose a 'discourse marketplace' model that demonstrates competing ways in which people frame diabetes care-seeking in India's medical pluralism, which includes allopathic and traditional systems of care. Four major domains emerged from grounded theory analysis: (1) normalization of diabetes in social interactions; (2) stigma; (3) stress; and (4) decision-making with regard to diabetes treatment. We found that participants selectively engaged with aspects of allopathic and non-allopathic Indian illness paradigms to build personalized illness meanings and care plans that served psychological, physical, and social needs. Participants constructed illness narratives that emphasized the social-communal experience of diabetes and, as a result, reported less stigma and stress due to diabetes. These data suggest that the pro-social construction of diabetes in India is both helpful and harmful for patients – it provides psychological comfort, but also lessens the impetus for prevention and self-care. Clarifying the social constructions of diabetes and chronic disease in India and other medically pluralistic contexts is a crucial first step to designing locally situated treatment schemes.